ChemInform Abstract: Exploring the Properties and Applications of Nanoceria: Is There Still Plenty of Room at the Bottom?. Issue 8 (February 2015) - Reed, Kenneth; Cormack, Alastair; Kulkarni, Aniruddha; Mayton, Mark; Sayle, Dean; Klaessig, Fred; Stadler, Brad
Abstract Review: 115 refs.